Retinal dysfunctions in a patient with a clinical high risk for psychosis and severe visual disturbances: A single case report. Issue 6 (21st December 2020) - Bernardin, Florent; Schwitzer, Thomas; Angioi‐Duprez, Karine; Giersch, Anne; Ligier, Fabienne; Bourion‐Bedes, Stéphanie; Jansen, Claire; Schwan, Raymund; Laprevote, Vincent
Abstract: Aim: Psychosis can be preceded by a clinical high risk for psychosis (CHR) and visual anomalies are predictors of transition to psychosis. Visual retinal processing is altered in psychosis, but no study has explored the links between visual symptoms and retinal functions in CHR patients. We report here the case of NR, an antipsychotic‐naive young adult with CHR and severe visual symptoms in whom we explored the retinal function. Methods: A flash electroretinogram (fERG) and a pattern electroretinogram (pERG) protocol were conducted and we compared NR results to a group of patients with schizophrenia and a group of healthy controls. Results: Despites an overlap between the measures of NR and the two groups, visual analyses revealed that NR showed increased b‐wave implicit time (rod response) compared to the control group and NR's response was at an intermediate level between two subgroups of schizophrenia patients regarding presence or absence of visual hallucinations. Discussion: The relevance of retinal dysfunctions as a marker of vulnerability for psychosis is discussed.